2018
DOI: 10.7566/jpsj.87.013704
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogap Behavior of the Nuclear Spin–Lattice Relaxation Rate in FeSe Probed by 77Se-NMR

Abstract: We conducted77 Se-nuclear magnetic resonance studies of the iron-based superconductor FeSe in magnetic fields of 0.6 to 19 T to investigate the superconducting and normal-state properties. The nuclear spin-lattice relaxation rate divided by the temperature (T1T ) −1 increases below the structural transition temperature Ts but starts to be suppressed below T * , well above the superconducting transition temperature Tc(H), resulting in a broad maximum of (T1T ) −1 at Tp(H). This is similar to the pseudogap behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…Recent NMR data found that anti-ferromagnetic spin fluctuations are present inside the nematic phase of FeSe 1−x S x , being strongest around x ∼ 0.1 [37]. In FeSe, spin fluctuations are rather anisotropic [37,38] and strongly field-dependent below 15 K [11]. Interestingly, the spin-fluctuations relaxation rate is enhanced below T * (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent NMR data found that anti-ferromagnetic spin fluctuations are present inside the nematic phase of FeSe 1−x S x , being strongest around x ∼ 0.1 [37]. In FeSe, spin fluctuations are rather anisotropic [37,38] and strongly field-dependent below 15 K [11]. Interestingly, the spin-fluctuations relaxation rate is enhanced below T * (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The low-temperature regime below T * displays linear resistivity, which is a potential manifestation of scattering induced by critical spin-fluctuations in clean systems [36]. µSR studies place FeSe near an itinerant antiferromagnetic quantum critical point at very low temperatures [12] and spinfluctuations are only found inside the nematic state [11,37]. On the other hand, close to the nematic end point in FeSe 1−x S x we find that resistivity is not linear in temperature but is dominated by a T 1.5 dependence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signatures of the preformed pairs with unusually strong pairing fluctuations above T c have been suggested by torque magnetometry [10] and nuclear magnetic resonance [11]. However, mean-field-like BCS behaviors are reported in other experiments [12,13].…”
mentioning
confidence: 92%
“…In fact, superconductingfluctuation effects on diamagnetic response observed in FeSe are unusually enhanced compared with those in conventional superconductors [4], which may be understood as caused by the strong attractive interaction [5]. In addition, recent NMR measurements have proposed that a pseudogap caused by the preformed-pair formation can exist, and that the onset temperature of the pseudogap depends on the magnetic-field strength [6]. The pair-formation field H * (T ) in FeSe has been estimated based on this NMR result [6] and also on thermodynamic and transport properties [4].…”
Section: Introductionmentioning
confidence: 99%